Assessment of Radio Protective Effects of Myrtus communis L. on Human Lymphocytes Irradiated in Vitro by Gamma-rays Using Micronucleus Assay on Binucleated Human Lymphocytes - Jouhmany, O.; Ebrahim, N.; Ikhtiar, A. (International Journal of Scientific Research in Biological Sciences, 2020)
The study aimed to investigate the potential protective effect of alcoholic extract of Myrtus communis L. leaves from the cytogenetic toxicity induced by gamma rays in human peripheral lymphocytes using micronucleus (MN) assay. Irradiation was done at a dose of 2 Gy and the extract was added to cell cultures at two different concentrations 50 and 100 µg/ml an hour before the irradiation of the samples. The results showed that the extract caused a decrease in frequency of MN due to the influence of gamma rays in the concentrations 50 and 100 ug / ml (P = 0.01) compared to the irradiated group. It was observed that concentration 50 µg/ml of the extract caused a greater decrease in the frequency of micronuclei compared to concentration 100 µg/ml, no significant differences were observed in frequency of micronuclei between two groups(p˃0.05).